CLINICIAN PERCEPTIONS OF SOCIAL WORKERS AND COMMUNITY HEALTH WORKERS IN PRACTICES CARING FOR FRAIL ELDERS. (8th November 2019) - Berrett-Abebe, Julie; Donelan, Karen; Auerbach, David I; Maramaldi, Peter; Berkman, Barbara
Abstract: Social workers (SW) and community health workers (CHW) have emerged as key workforce personnel in efforts to care for elders in the U.S. However, little is known about the presence and roles of these professionals in outpatient practices. This paper presents findings from a nationally representative survey of geriatrics and primary care practices. Key findings include: reported challenges in meeting the social service needs of elders, underutilization of SW, and fuller utilization of social work competencies in practices in which both SW and CHW were present. These findings offer a unique perspective of SW on interprofessional teams and have implications for the future of the profession.